2003
DOI: 10.1097/01.icl.0000086490.38331.58
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline in the Management of Pseudomonas Corneal Melting

Abstract: Tetracyclines have an anticollagenolytic action in addition to their antimicrobial activity. The use of doxycycline as an adjunctive therapy in the management of Pseudomonas corneal melting may help to stabilize corneal breakdown and prevent subsequent perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Other MMPs also had highly upregulated gene expression in both BK and FK, including MMP10, blockade of which improves corneal epithelial healing in diabetic corneas (Saghizadeh et al, 2013). Pharmacological inhibition of MMPs with tetracyclines has shown some success toward halting corneal perforation in both animal models and human MK, and thus may prove to be a potential therapeutic target (Levy and Katz, 1990; McElvanney, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Other MMPs also had highly upregulated gene expression in both BK and FK, including MMP10, blockade of which improves corneal epithelial healing in diabetic corneas (Saghizadeh et al, 2013). Pharmacological inhibition of MMPs with tetracyclines has shown some success toward halting corneal perforation in both animal models and human MK, and thus may prove to be a potential therapeutic target (Levy and Katz, 1990; McElvanney, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) is one group of proteases, which include collagenases, gelatinases, and stromelysins. [3233] Inhibition of MMPs may be helpful in the prevention of stromal destruction. Proposed MMP inhibitors which have been proposed for use in microbial keratitis include tetracyclines, acetylcysteine, ascorbate, and sodium ethylenediaminetetraacetic acid.…”
Section: Matrix Metalloproteinases Inhibitorsmentioning
confidence: 99%
“…McElvanney[33] reported two cases of culture-proven pseudomonas bacterial keratitis treated oral doxycycline 100 mg twice daily, in addition to topical ofloxacin 0.3% and ceftazidime 5%. He found that stabilization of corneal melting occurred, but this report offers little or nothing in regard to evidence of the benefit of doxycycline.…”
Section: Matrix Metalloproteinases Inhibitorsmentioning
confidence: 99%
“…The use of anti‐collagenase treatment, such as medroxyprogesterone (MPG) may have a protective role or serve to reduce the severity of the condition. Oral tetracycline also prevents corneal melting . This form of treatment has been used in several studies following corneal graft procedures.…”
Section: Treatmentmentioning
confidence: 99%